Effect of flow velocity on corrosion behaviour of spark plasma sintered Fe-Cr-Ni reinforced with TiN in 3.5 wt% NaCl. (2021) - Ige, O.O.; Oke, S.R.; Falodun, O.E.; Aribo, S.; Oluwasegun, K.M.; Ajibola, O.O.; Olawale, J.O.; Ogunbadejo, A.; Olalemi, O.T.; Olubambi, P.A.
Abstract: This study investigated the effect of varying flow velocities on the corrosion behavior of titanium nitride reinforced Fe-Cr-Ni (Duplex Stainless Steel – UNS S32205) manufactured by spark plasma sintering. The TiN reinforcement was within the range of 0–8% at an interval of 2%. The spark plasma sintering parameters are sintering temperature (1150 °C), sintering time (10 mins), applied pressure (50 Mpa) and heating rate (100 °C/mins). The sintered samples were subjected to both gravimetric and electrochemical measurement in 3.5 wt% NaCl at a flow velocity of 1.0 m/s and increasing at 0.5 m/s till 2.5 m/s. A field emission scanning electron microscope (FESEM) equipped with energy dispersive x-ray spectrometer (EDS) was employed to carry out the microstructural characterizations of the corroded sintered products. The results showed that increasing the flow velocity decreased the passive current, but leads to more positive corrosion potential of the sintered products. The active-passive behaviour and the role of microstructures on the reinforced sintered composites in 3.5 wt% NaCl are discussed.